1988
DOI: 10.1111/j.1476-5381.1988.tb11667.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of action of nicotine in isolated urinary bladder of guinea‐pig

Abstract: 1 Nicotine produced a transient contraction of isolated strips of guinea-pig urinary bladder. The response to nicotine was antagonized by the nicotinic receptor antagonist, hexamethonium but was insensitive to tetrodotoxin.2 The nicotine-induced contraction was potentiated by the cholinesterase inhibitor, physostigmine, and was reduced to 50% and 70% by the muscarinic cholinoceptor antagonist, atropine and the sympathetic neurone blocking drug, guanethidine, respectively. Chemical denervation with 6-hydroxydop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 25 publications
5
22
1
Order By: Relevance
“…The concentration of nicotine required for a 50% contractile response was 51 (31-86) AM. Consistent with previous observations (Hisayama et al, 1988), the nicotine-induced contractions were reduced by pretreatment with atropine or hexamethonium, a ganglionic nicotinic antagonist (preliminary observation, N = 3), indicating that nicotine stimulated the intramural parasympathetic ganglion cells to induce the release of ACh from the post-ganglionic nerve terminals, although it has been reported that intramural ganglion cells are not so abundant in the guinea pig bladder (Gabella, 1990). We chose a nicotine concentration of 100 AM to investigate the effects of the AChE inhibitors in this study.…”
Section: Concentration-response Of Nicotine-induced Detrusor Contractsupporting
confidence: 94%
“…The concentration of nicotine required for a 50% contractile response was 51 (31-86) AM. Consistent with previous observations (Hisayama et al, 1988), the nicotine-induced contractions were reduced by pretreatment with atropine or hexamethonium, a ganglionic nicotinic antagonist (preliminary observation, N = 3), indicating that nicotine stimulated the intramural parasympathetic ganglion cells to induce the release of ACh from the post-ganglionic nerve terminals, although it has been reported that intramural ganglion cells are not so abundant in the guinea pig bladder (Gabella, 1990). We chose a nicotine concentration of 100 AM to investigate the effects of the AChE inhibitors in this study.…”
Section: Concentration-response Of Nicotine-induced Detrusor Contractsupporting
confidence: 94%
“…One mechanism to explain the association of current smoking with urgency could be nicotine, which has been shown to produce phasic contraction of the urinary bladder in animal models [30, 31]. Another suggestion for the association could be the effect of ischaemia caused by smoking on detrusor function [32].…”
Section: Discussionmentioning
confidence: 99%
“…Nicotine determines contraction through activation of nicotinic receptors of the parasympathetic neurons in parasympathetic ganglia, that are known to be present within the bladder wall [1] . Moreover, nicotinic receptors are located on other nerve terminals and modulate exocytosis of neurotransmitters acting on detrusor contractile function [16] ; this could explain the dose-dependent contractile response to nicotine of rat detrusor, which is reported to be poor of intramural ganglia [17] .…”
Section: Discussionmentioning
confidence: 99%